KEY DRIVERS OF DEFORESTATION IN PEHANG MALAYSIA: A THREAT TO TROPICAL FOREST ECOSYSTEM - Mande, Hosea Kato (FUDMA JOURNAL OF SCIENCES, 2020)
The growing population is often associated with various environmental disturbances which have been altering the natural earth ecosystem and numerous land development activities have made the existing forests suffer deforestations. The aim of the research is to ascertain the key drivers of deforestation. The techniques employed are landsat TM, SPOT-5and land use map. Deforestation rates between 1990 and 2010 indicated total deforestation occurred between 1995 and 2000 of 7.59% at a rate of 0.04 ha/year, follow by the year 2005 to 2010 with 6.74% at a rate of 0,032ha/year. The lowest deforestation was recorded between 1990 and 1995 with 0.38% at a rate of 0.002 ha/yr while the total deforestation for the entire 30 years was 16.98% at an average rate of 0.020 ha/yr. The deforestation rates in Pahang have been  estimated to occurred between years 1990 and 2010  ranging from 0.002 - 0.04 million ha/yr. These results demonstrated that Pahang is still characterized by high forest cover and slow deforestation rates. However, commercial agriculture was estimated to be the first single driver of deforestation, which accounted for about 80% of deforestation compared to other drivers. The finding concluded that commercial agricultural such as palm oil plantation and rubber plantation was the main proximate drivers for the deforestation in Pahang. It was demonstrated that the integration of multi temporal datasets from Landsat-TM andSPOT-5 satellite images with landuse maps was capable in identifying direct drivers of deforestation. However, extensive use of ground thruting will compliment the landsat, SPOT-5and the landuse map.